Dynamic Strategy Selection in Collaborative Spatial Tasks. Issue 8 (17th November 2018) - Galati, Alexia; Panagiotou, Elisavet; Tenbrink, Thora; Avraamides, Marios N.
ABSTRACT: When speakers coordinate with one another, they have available a range of alternatives for conceptualizing and describing spatial relationships. To understand the features of successful communication in collaborative spatial tasks, it is important to identify factors that shape speakers' linguistic choices and evaluate them in relation to task success. In this article we examine how description strategies—in particular, references to global versus local conceptualizations of spatial relationships—change over time, how the use of these strategies is related to both contextual cues and the partner's feedback, and finally how these factors affect communicative success in terms of efficiency and accuracy in the task. In the dialogue task we used, Directors described from memory a spatial layout with intrinsic properties to a Matcher who reconstructed it based on those descriptions. We found that global description strategies and feedback from the Matcher that contributed to grounding (such as recaps) predicted better task performance, whereas local description strategies and queries from the Matcher predicted poorer performance. Importantly, the strategy adopted by pairs early in the dialogue predicted their ultimate accuracy in reconstructing the layout. This work underscores that to unpack the complex factors that contribute to successful communication, it is important to consider not only the linguistic strategies that speakers use, but also how these unfold over time and are shaped by interactive processes, such as those reflected by the partner's feedback.